If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4(x + 3) = 68 Reorder the terms: 3x + 4(3 + x) = 68 3x + (3 * 4 + x * 4) = 68 3x + (12 + 4x) = 68 Reorder the terms: 12 + 3x + 4x = 68 Combine like terms: 3x + 4x = 7x 12 + 7x = 68 Solving 12 + 7x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7x = 68 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 68 + -12 7x = 68 + -12 Combine like terms: 68 + -12 = 56 7x = 56 Divide each side by '7'. x = 8 Simplifying x = 8
| 3x-8+x+12=17 | | -15*5/3c*8 | | -5(2x-1)=3(x+5) | | 56y+1=781 | | 6x+8=290 | | -3+1=x+9-4x | | v/4-10=5 | | 1.5x-18=0.5x | | 22/11x9-3 | | -4/3+x2+1/3x-8+8/3x | | 5v^2=20 | | 2/63/6= | | (2r-4s+6t)(2r-4s+6t)= | | 5y+y-9=8y+1 | | 4+12/4-2 | | 80x^2=50 | | 3(a-5)=6a(3a+15) | | -4/3+t2+1/3t-8+8/3t | | (a/6)-11=25 | | (3xy^2)(-5x^3y)= | | 4x-25x^1/2+25=0 | | 8x-36=8 | | ax-bx=-cforx | | -20c+3-3c+13= | | x-.20=64 | | 6.8x-4.7=17.62 | | 4x-25x^1/2+25 | | -12x+4-6x=2x+7x-3 | | -5b+24=-17+2x | | Y=-.25(1)+3 | | 2x^6+20x^5+48x^4=0 | | -2(t-7)-(t-5)=5 |